The Banality of Digital Reputation: A Visual Ethnography of Young People, Reputation, and Social Media - De Ridder, Sander (2021)
This article relies on a visual ethnography with young people between 13 and 20 years old. Young people were asked to make visual collages of fictional social media accounts, which are used in this article to analyse the signification of “good” and “bad” reputation in digital youth culture. It explores how reputation is performed visually and aesthetically in digital youth culture. The aim is to contribute to the critical study of digital reputation, it formulates an ethical critique on how the signification of digital reputation has formed alongside values and beliefs that support the growth of platform capitalism, rather than assigning a reputational value and rank responsibly. I conclude how the signification of digital reputation is not only conformist and essentialist but also meaningless. The banality of reputation argues that, in the context of popular social media, there is no real or substantial information made available to distinguish between a “good” or a “bad” reputation, except for stylized banality, a stylistic focus on lifestyle and commodities. The point is that reputation should not be banal and meaningless. Many important political and institutional decisions in a democracy rely on the evaluation of reputation and critical assessment of the information upon which such evaluations are made. Although platform capitalism has made digital reputation meaningless, it is in fact an essential skill to critically orient oneself in digital societies.